(3gOGjI GdSGdc Edi eYQaI GdePGgH GdCQHYI aj GdefGScs - (3YHO GdYRjR Hf eMeO Hf EHQGgje, GHf LeGYI GdcfGfj, GdMehj GdCUd, GdOeTbj GdehdO, Ke GdeUQj, YR GdOjf,J (B767 (3g` s ((3ecI GdecQeI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQY dbGUOjg CbUO WQjb GeG HYO aEf GdML YHGOI TQYJ eGdjI hHOfjI hLeYJ CfhGY GdJYHO bhdG hYedG hfjI s
(3BNQgG (B:s
(3aPdc YdGeI GdbHhd hHdhZ GdeCehd fSGd Gddg JYGdi GdJhajb Je GdcJGH hddg GdMeO hGdefI s
(3HChdgG agQS YdjgG ebGHdI Ydi GUd eYJeO ai faS SfI GdfSN hGdhQbI GdChdi efgG hGhQGb HOGNdgG HNW eZGjQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B257s
Keywords: (3CUhd Gdabgs